DRUG UTILIZATION EVALUATION AND COST ANALYSIS OF ANTIEMETIC DRUGS PRESCRIBED IN ONCOLOGY WARD IN A QUATERNARY CARE HOSPITAL - Nishita, Ardeshna A; Rispa, Darabadi; Harshini Y, Reddy; R, Srinivasan (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Drug utilization is defined by the World Health Organization as the marketing, distribution, prescription, and use of drugs in society, with special emphasis on the resulting medical, social, and economic consequences. Our study is done to obtain the variation of drug use and costs of drug therapy, from which medical and social qualitative consequences can be found. Our study emphasizes on knowing the drug utilization and cost included for antiemetics in patients undergoing chemotherapy in oncology ward. Methods: It was observational, prospective and non-interventional study. Results: Total of 141 patients were studied, out of which 77 (54.6%) patients were female and 64 (45.4%) patients were males. The majority of the patients in this study belong to the age group of 40-49 (29%) and 60-69 (20%) years. The comparison with the standard protocol was made according to the use of antiemetics in the patients. Out of which, 137 (97%) patient profiles were found to be deviating from standard protocol, and 4 (3%) patient profiles were found following the standard protocol because of including prochlorperazine which is not mentioned in the standard protocol. Conclusion: As of future approach, education to physician for rational drug use and review of medication chart with patient consideration can give better health care and also cost effective treatment. Keywords: Drug use evaluation, Antiemetics, Chemotherapy.